STUDIES ON CAPTURE PROCESS AND FISH BEHAVIOUR TOWARDS MILLENNIUM GILL NET IN BONDET WATERS, CIREBON - Carolina Catur Rakhmadevi; Ari Purbayanto; Muhammad Fedi Alfiadi Sondita (Indonesian Fisheries Research Journal, 2008)
The millennium gill net was recently adopted by Cirebon fishermen. lts use has been spread to other areas. Research on this type of gear has been rare. The objectives of this research were to investigate the effects of transparency on the fish behaviour towards net panel of millennium gill net and to obtain the information on catch composition and the capture process of millennium gill net.